Laparoscopic treatment for an intrapancreatic accessory spleen: A case report - Zhang, Yihan; Shi, Guodong; Meng, Lingdong; Wu, Jing; Hu, Qingqiao; Xv, Dong; Zhang, Kai; Lu, Zipeng; Wu, Junlii; Jiang, Kuirong (Frontiers in Oncology, 2022)
Malignant pancreatic tumors have early metastasis, aggressive behavior and poor prognosis. Surgeons often need to judge whether a patient needs prompt surgery when a pancreatic lesion is found. The accessory spleen is a congenital developmental malformation rather than a tumor and does not require surgical resection. Here, we report a 47-year-old man who underwent routine gastroscopic examination, and a submucosal eminence of the duodenal bulb was detected. The patient was asymptomatic and laboratory tests were unremarkable. Duodenal neuroendocrine neoplasm (G2) was considered following endoscopic submucosal dissection (ESD). Further examination showed a lesion in the tail of the pancreas and multiple accessory spleens. The lesion in the tail of the pancreas was Ga-68 positive and was highly considered a pancreatic neuroendocrine tumor (pNET). Based on this clinical evidence, laparoscopic spleen-preserving distal pancreatectomy (Kimura) was performed. However, the results of the postoperative pathological diagnosis indicated an intrapancreatic accessory spleen (IPAS). Given the findings of this case, we should explore more accurate diagnostic methods for IPAS to avoid unnecessary surgery.